The relevance of Muhammad Baqir Al-sadr’s thought on zakat distribution for poverty alleviation in Indonesia - Al Berto, Muhammad; Mugiyati; Al-farisy, Muhammad Daffa (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
Poverty remains a major challenge in Indonesia despite institutionalized zakat management. Muhammad Baqir al-Sadr conceptualizes zakat as a productive redistributive mechanism intended to promote long-term socioeconomic justice. This study assesses the effectiveness of zakat within this framework using the Autoregressive Distributed Lag (ARDL) approach with annual data from 2001–2023 and GDP as a control variable. The results indicate that zakat has a significant short-run effect, reducing poverty with its strongest impact appearing after a lag (coefficient = –0.131), although the effect weakens and reverses over time, reflecting a consumption-based distribution pattern. In contrast, GDP shows both short-run and long-run significance in lowering poverty, with a sustained negative long-term effect (coefficient = –0.855). These findings suggest that current Zakat implementation has not yet embodied al-Sadr’s productive model and requires governance reforms to strengthen its structural role in poverty alleviation.